DINAMIKA HISTORIS BARAT-ISLAM: MISPERSEPSI, PRASANGKA, DAN KONFLIK - Syahirul Alim (UIN Syarif Hidayatullah Jakarta, 2020)
Absract. The historical dynamics of the West-Islam always depicted as a phenomenon of misperception, antipathy, and conflicts that have been going on since the 12th century. The events of the Crusades and the spirit of reconquest of areas once occupied by Islam, leaving a bad-trail imprint in almost all perspectives of Western society towards Islam. Western antipathy was shown through negative sentiments, such as the term